Programme for stage-by-stage monitoring of young hockey players' motor skills - Medvedev, V.G.; Davydov, A.P. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to develop a programme for stage-by-stage monitoring of the motor skills of young hockey players. Methods and structure of the study. The rationale for the stage-by-stage monitoring programme was developed with the participation of 135 hockey players aged 9-19 years of varying skill levels and positions. Results and conclusions. The programme for phased monitoring included special tests performed on ice and tests performed off ice. The article presents a list of tests selected in the course of many years of research, as well as informative indicators for each test. The assessment system includes standards developed for different age groups in accordance with the stages of sports training for hockey players. The proposed stage control programme is recommended for use in the training process at the beginning and end of each academic year (season), and, if necessary, additionally during the year.